Automation and Cybersecurity: Creating a Testing Tool for SDN Networks - Leal, Ryan M. S.; Freitas, Johan K. E.; Albuquerque Júnior, Francisco A. C.; Lopes, Waslon T. A.; Carvalho, Fabrício B. S.; Fonseca, Iguatemi E. (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2024: Companion Proceedings of the 24th Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2024.241892, 2024)
With the widespread adoption of Software Defined Networks (SDN) in various current applications, increasingly more methods of vulnerability exploitation have been created targeting the data, control, and application planes. Due to its characteristic of centralizing control logic, SDN networks are more susceptible to denial-of-service attacks, thereby heightening the need to improve network protection methods. Aiming to contribute to the understanding of cyberattacks in SDN networks, this work demonstrates the development of an automated and modular testing execution tool, allowing for the customization of tests and ease of use in SDN network management routines.